Peningkatan Nilai Moral Kejujuran Siswa Tingkat SMP Melalui Model Value Clarification Technique (VCT) - Salsa Augustila; Muhammad Salam; Tohap Pandapotan Simaremare (Journal of Civic Education, 2022)
The purpose of this research was to find out whether the application of the Value Clarification Technique (VCT) model was effective and could increase the moral value of honesty. The research design is a classroom action research (CAR) with three cycles. The research subjects were students and teacher in class VIII G students of SMP N 9 in Jambi City. The object of research is the level of student honesty that measured by some questions. The results showed that there are increasing percentage of the average value in each cycle of process. It can be concluded that the use of the VCT model with the help of interactive videos and student worksheets on honesty can increase the value of honesty. Though this increase does not occur evenly in all students and there is some obstacles such as the internet connection when using the video interactive in classroom.